Financial ratios as predictor of corporate financial distress (trend analysis and logistic regression approach) / Khairul Anuar Kamarudin - Kamarudin, Khairul Anuar (2000)
This dissertation examines financial ratios as a tool of predicting financial distress. The classical Beaver (univariate model) and Altman (multivariate model) are tested in this research on Malaysian environment. In doing so, the dissertation discloses the response of Altman and Beaver towards economic recession. The empirical method covers the period 1990-8. From generated Z-Score and Beaver ratio, the patterns show that both models respond very well during economic recession. However, the trend analysis conducted in this study failed to detect any early signals of financial distress. The results from the logistic regression approach confirmed the conclusion made for trend analysis. Majority of the financial ratios in Altman model are insignificant in predicting financial distress in the last three years before the economic recession. The insignificance of the financial ratios in Altman model do not totally reject the model but calls for new coefficient and more appropriate ratios in future research.